Entropies of thymocytogram, splenocytogram, immunocytogram and leukocytogram in rats are regulated by sex and the neuroendocrine parameters while regulates immune parameters - Volodymyra Bilas; Oleksandr Popadynets'; Igor-Severyn Flyunt; Nadiya Sydoruk; Nataliya Badiuk; Serhiy Gushcha; Walery Zukow; Anatoliy Gozhenko; Igor Popovych (Kazimierz Wielki University, 2020)
Background. We have previously shown that the Entropy (E) of the relative spectral power density (SPD) of the EEG rhythms is its quite relevant parameter. We also found significant relationships between the SPD E of individual EEG loci and the E of the Leukocytogram (LCG) and Immunocytogram (ICG) of the blood, as well as with their individual components. The purpose of this study was to clarify the relationships between E(s) of these four morpho-functional immune subsystem and sex as well as parameters of the neuroendocrine-immune complex in rats. Materials and methods. Experiment was performed on 108 healthy Wistar rats (48 male and 60 female) weighing 205-300 g (M±SD=260±26 g) divided into 8 groups. Animals of the first group remained intact, using tap water from drinking ad libitum. Instead, the other rats received various balneofactors for 6 days. The day after the completion of the drinking/application course in all rats the parameters of neuroendocrine-immune complex were registered. Results. The drinking/application course did not affect the E level of any morpho-functional immune subsystem, the relationships between which are insignificant.